Tropical Vegetation and Land Cover Mapping Using LiDAR - Nurcholis, Mohammad; Himawan, Iwan Qodar; Wijayanti, Syintianuri Intan; Darmaristianti, Ayu (Universitas Muhammadiyah Yogyakarta, 2019)
LiDAR (Light Detection and Ranging) is a system of active remote sensing technology using a laser beam that has an invisible wave (Infrared) that can penetrate the leaf gap to produce topographic characteristics of the land surface. The research locations were in Tunas Baru Village Sekernan District, Muaro Jambi Regency, Jambi Province. The purpose of this study was to apply Airborne LiDAR technology along with interpretations in agriculture, especially land cover vegetation mapping in Jambi Province, which is a province that has a fairly extensive forest area. Speaking of that situation, a land cover map and classification are needed to find out which vegetation is dominant in the area. The data needed in this professional work class were DEM, DSM and orthophoto data to be processed into CHM (dataCrown Height Model) in order to facilitate digitization in determining density classes. At the same time, orthophoto was used to digitize the classification of vegetation types, which will produce output in the form of a map of land cover in Tunas Baru Village, Sekernan District, Muaro Jambi Regency, Jambi Province.